Jasmonate- and salicylate-mediated plant defense responses to insect herbivores, pathogens and parasitic plants - Smith, J.L.; De Moraes, C.M.; Mescher, M.C.
While extensive research has examined plant defense responses to attack by herbivores and pathogens, plant responses to parasitism by other plants are not well characterized. The expression of induced plant defenses is mediated by complex signaling networks inwhich the plant hormones jasmonic acid (JA)and salicylic acid (SA)play key roles. In general, JA-mediated signaling pathways are implicated in the regulation of antiherbivore defenses,while the SA pathway is associated with defense responses against pathogens. However, there are many exceptions to this basic framework, and recent work suggests that interactions between the JA and SA pathways may play important roles in fine-tuning defense responses. The few studies that have addressed plant responses to parasitism by other plants suggest that both salicylates and jasmonates can mediate effectivedefenses. Here, a review is given of recentwork on these defense signalingmolecules with relevance for understanding their role in plant responses to parasitism.
Keywords: PARASITIC PLANTS; PLANT SIGNALING; JASMONIC ACID; SALICYLIC ACID; CROSS-TALK